Swarm / 2 - Westerfeld, Scott (Westerfeld, Scott. Zeroes, 2018)
As they celebrate the opening of their underground nightclub, the Zeroes, six teenagers with unique abilities, learn about the sinister power of Swarm, who uses a crowd's rage to kill--and who loves killing Zeroes.